Standard area diagram set to assess scab severity in entire-margined leaves of sour passion fruit - Brás, Verônica Vieira (Universidade Federal de Viçosa, 2020)
Scab, caused by Cladosporium cladosporioides complex, is one of the most important diseases affecting passion fruit yield and fruit quality. The assessment of plant diseases is important to determine their correct management and the standard area diagrams (SADs) are useful tools to achieve this goal. This study aimed to develop and validate a SAD to quantify the severity of scab in entire-margined leaves of sour passion fruit. The SAD obtained has ten images of scab severity values (0.4, 3.5, 5.4, 8.0, 11.1, 16.2, 26.1, 38.2, 47.9, and 58.9%). To evaluate the SAD, twenty raters were involved (ten experienced (EP) and ten inexperienced (IP)) who estimated the same set of fifty images twice being first without and after with the use of the SAD. The accuracy was significantly improved by using SAD. The coefficient of bias (C b ) were 0.75 and 0.98 for IP and 0.96 and 0.98 for EP without and with SAD, respectively. The correlation coefficient (r) was 0.89 and 0.97 for IP and 0.95 and 0.97 for EP without and with SAD, respectively. Lin's concordance correlation coefficient (ρ c ) were 0.66 and 0.95 for IP and 0.91 and 0.95 for EP without and with SAD, respectively. Moreover, the coefficient of determination (R 2 ) was significantly improved by using SAD. The SAD proposed will improve the accuracy and precision during the evaluation of scab severity in entire-margined leaves of sour passion fruit. Keywords: Accuracy. Epidemiology. Foliar disease. Phytopatometry. Scab quantification.

A verrugose, causada por fungos do complexo Cladosporium cladosporioides, é uma das doenças mais importantes afetando a produção do maracujazeiro e a qualidade dos frutos. A avaliação das doenças de plantas é importante para realizar o manejo correto e as escalas diagramáticas são ferramentas úteis para isso. Este estudo teve como objetivo elaborar e validar uma escala diagramática para quantificar a severidade da verrugose em folhas com margens inteiras de maracujazeiro. A escala obtida contém dez imagens com valores de severidade (0,4; 3,5; 5,4; 8,0; 11,1; 16,2; 26,1; 38,2; 47,9 e 58,9%). Para avaliar a escala, vinte avaliadores foram envolvidos (dez experientes (EP) e dez inexperientes (IP)), os quais estimaram o mesmo conjunto de cinquenta imagens, duas vezes, primeiro sem e depois com a escala. A acurácia aumentou significativamente usando a escala. O coeficiente de viés (C b ) foi 0,75 e 0,98 para IP e 0,96 e 0,98 para EP, sem e com a escala, respectivamente. O coeficiente de correlação (r) foi 0,89 e 0,97 para IP e 0,95 e 0,97 para EP, sem e com a escala respectivamente. O coeficiente de correlação concordante de Lin foi 0,66 e 0,95 para IP e 0,91 e 0,95 para EP, sem e com a escala, respectivamente. Além disso, o coeficiente de determinação (R 2 ) aumentou significativamente usando a escala. A escala proposta aumentará a acurácia e a precisão durante a avaliação da severidade da verrugose em folhas com margens inteiras de maracujazeiro. Palavras-chave: Acurácia. Doença foliar. Epidemiologia. Fitopatometria. Quantificação da verrugose.
Escala diagramática para avaliar a severidade da verrugose em folhas de margens inteiras de maracujazeiro azedo
Keywords: Maracujá - Doenças e pragas; Folhas - Análise; Epidemiologia; Verrugose; Fitopatologia